The Digital Dilemma: Intellectual Property in the Information Age - National Research Council (The National Academies Press, 2000)
Imagine sending a magazine article to 10 friends-making photocopies, putting them in envelopes, adding postage, and mailing them. Now consider how much easier it is to send that article to those 10 friends as an attachment to e-mail. Or to post the article on your own site on the World Wide Web. The ease of modifying or copying digitized material and the proliferation of computer networking have raised fundamental questions about copyright and patent—intellectual property protections rooted in the U.S. Constitution. Hailed for quick and convenient access to a world of material, the Internet also poses serious economic issues for those who create and market that material. If people can so easily send music on the Internet for free, for example, who will pay for music? This book presents the multiple facets of digitized intellectual property, defining terms, identifying key issues, and exploring alternatives. It follows the complex threads of law, business, incentives to creators, the American tradition of access to information, the international context, and the nature of human behavior. Technology is explored for its ability to transfer content and its potential to protect intellectual property rights. The book proposes research and policy recommendations as well as principles for policymaking.
Keywords: Behavioral and Social Sciences; Policy for Science and Technology

Education and Delinquency: Summary of a Workshop - National Research Council; Institute of Medicine (The National Academies Press, 2000)
The Panel on Juvenile Crime: Prevention, Treatment, and Control convened a workshop on October 2, 1998, to explore issues related to educational performance, school climate, school practices, learning, student motivation and commitment to school, and their relationship to delinquency. The workshop was designed to bring together researchers and practitioners with a broad range of perspectives on the relationship between such specific issues as school safety and academic achievement and the development of delinquent behavior. Education and Delinquency reviews recent research findings, identifies gaps in knowledge and promising areas of future research, and discusses the need for program evaluation and the integration of empirical research findings into program design.
Keywords: Behavioral and Social Sciences

Improving Intergroup Relations Among Youth: Summary of a Research Workshop - National Research Council; Institute of Medicine (The National Academies Press, 2000)
On November 9-10, 1998, the Forum on Adolescence of the Board on Children, Youth, and Families, a cross-cutting initiative of the Institute of Medicine and the National Research Council of the National Academy of Sciences, convened a workshop entitled Research to Improve Intergroup Relations Among Youth. Held at the request of the Carnegie Corporation of New York, this workshop considered selected findings of 16 research projects that have focused on intergroup relations among children and adolescents; all 16 received funding from Carnegie Corporation of New York for their work on this issue. The funding of these projects was part of a larger research initiative supported by Carnegie Corporation of New York that sought to update and expand the knowledge, sources, and dynamics of racial and ethnic prejudice among youth, identifying approaches to foster intergroup understanding. Improving Intergroup Relations Among Youth is the summary of the workshop, which provided an opportunity to learn about the work and preliminary findings of the 16 projects. This report reviews the knowledge base regarding the effectiveness of interventions designed to promote peaceful, respectful relations among youth of different ethnic groups.
Keywords: Behavioral and Social Sciences

Early Childhood Intervention: Views from the Field: Report of a Workshop - National Research Council; Institute of Medicine (The National Academies Press, 2000)
On June 24-25, 1999, the Committee on Integrating the Science of Early Childhood Development of the Board on Children, Youth, and Families of the National Research Council/National Academy of Sciences and the Institute of Medicine convened a workshop for researchers and practitioners to examine the underlying knowledge base that informs current best practices in early childhood services, from the prenatal period to school entry. Early Childhood Intervention discusses the diversity of working assumptions, theories of change, and views about child development and early intervention that currently shape a wide variety of social policies and service delivery systems for young children and their families.
Keywords: Behavioral and Social Sciences; Health and Medicine

From Neurons to Neighborhoods: The Science of Early Childhood Development - Institute of Medicine; National Research Council (The National Academies Press, 2000)
How we raise young children is one of today's most highly personalized and sharply politicized issues, in part because each of us can claim some level of "expertise." The debate has intensified as discoveries about our development—in the womb and in the first months and years—have reached the popular media. How can we use our burgeoning knowledge to assure the well-being of all young children, for their own sake as well as for the sake of our nation? Drawing from new findings, this book presents important conclusions about nature-versus-nurture, the impact of being born into a working family, the effect of politics on programs for children, the costs and benefits of intervention, and other issues. The committee issues a series of challenges to decision makers regarding the quality of child care, issues of racial and ethnic diversity, the integration of children's cognitive and emotional development, and more. Authoritative yet accessible, From Neurons to Neighborhoods presents the evidence about "brain wiring" and how kids learn to speak, think, and regulate their behavior. It examines the effect of the climate—family, child care, community—within which the child grows.
Keywords: Behavioral and Social Sciences; Education

LC21: A Digital Strategy for the Library of Congress - National Research Council (The National Academies Press, 2000)
Digital information and networks challenge the core practices of libraries, archives, and all organizations with intensive information management needs in many respects—not only in terms of accommodating digital information and technology, but also through the need to develop new economic and organizational models for managing information. LC21: A Digital Strategy for the Library of Congress discusses these challenges and provides recommendations for moving forward at the Library of Congress, the world's largest library. Topics covered in LC21 include digital collections, digital preservation, digital cataloging (metadata), strategic planning, human resources, and general management and budgetary issues. The book identifies and elaborates upon a clear theme for the Library of Congress that is applicable more generally: the digital age calls for much more collaboration and cooperation than in the past. LC21 demonstrates that information-intensive organizations will have to change in fundamental ways to survive and prosper in the digital age.
Keywords: Behavioral and Social Sciences; Education

International Conflict Resolution After the Cold War - National Research Council (The National Academies Press, 2000)
The end of the Cold War has changed the shape of organized violence in the world and the ways in which governments and others try to set its limits. Even the concept of international conflict is broadening to include ethnic conflicts and other kinds of violence within national borders that may affect international peace and security. What is not yet clear is whether or how these changes alter the way actors on the world scene should deal with conflict:
Keywords: Conflict and Security Issues; Behavioral and Social Sciences

Beyond Six Billion: Forecasting the World's Population - National Research Council (The National Academies Press, 2000)
Is rapid world population growth actually coming to an end? As population growth and its consequences have become front-page issues, projections of slowing growth from such institutions as the United Nations and the World Bank have been called into question. Beyond Six Billion asks what such projections really say, why they say it, whether they can be trusted, and whether they can be improved. The book includes analysis of how well past U.N. and World Bank projections have panned out, what errors have occurred, and why they have happened. Focusing on fertility as one key to accurate projections, the committee examines the transition from high, constant fertility to low fertility levels and discusses whether developing countries will eventually attain the very low levels of births now observed in the industrialized world. Other keys to accurate projections, predictions of lengthening life span and of the impact of international migration on specific countries, are also explored in detail. How good are our methods of population forecasting? How can we cope with the inevitable uncertainty? What population trends can we anticipate? Beyond Six Billion illuminates not only the forces that shape population growth but also the accuracy of the methods we use to quantify these forces and the uncertainty surrounding projections. The Committee on Population was established by the National Academy of Sciences (NAS) in 1983 to bring the knowledge and methods of the population sciences to bear on major issues of science and public policy. The committee's work includes both basic studies of fertility, health and mortality, and migration; and applied studies aimed at improving programs for the public health and welfare in the United States and in developing countries. The committee also fosters communication among researchers in different disciplines and countries and policy makers in government, international agencies, and private organizations. The work of the committee is made possible by funding from several government agencies and private foundations.
Keywords: Behavioral and Social Sciences; Health and Medicine

Who Will Do the Science of the Future?: A Symposium on Careers of Women in Science - National Academy of Sciences; National Research Council (The National Academies Press, 2000)
Who Will Do the Science of the Future? is the summary of a symposium on careers of women in science. The symposium incorporated three panels of presenters: one focusing on the next generation, Science for All Students; a second that looks in depth at the issues reflected in one particular field of science, computer science, reflecting an in-depth view of academic and industrial computer scientists; and a third that focuses on strategies and policies to recruit, retain, and promote career advancement for women scientists. Lastly, there was a plenary address on how to ensure women continue to advance into positions of leadership in science.
Keywords: Behavioral and Social Sciences; Industry and Labor

Time-Use Measurement and Research: Report of a Workshop - National Research Council (The National Academies Press, 2000)
One of the most substantial policy changes in the past decade was the elimination of the main social welfare program for poor families, Aid to Families with Dependent Children, ending the entitlement to cash benefits and replacing it with a policy emphasizing work. A question relevant for understanding the consequences of this policy change is how the time allocation among work and family care activities of poor families has changed. President Clinton's proposed budget for fiscal 2001 includes funds for the Bureau of Labor Statistics (BLS) to develop a survey to measure how Americans spend their time (U.S. Department of Labor, 2000). BLS has already explored the feasibility of such a survey. In 1997, a pilot study that collected time-use data for a sample of Americans was conducted, and the results of that study were presented at a 1997 conference sponsored by BLS and the MacArthur Network on the Family and the Economy. Using knowledge gained from the pilot study and the conference, BLS published a report on the feasibility of a national time-use survey and developed a proposal to conduct the survey. Time-Use Measurement and Research is a summary of a workshop convened to consider data and methodological issues in measuring time use. This report discusses why time-use data are needed, highlighting many of policy and behavioral applications of time-use data. It also summarizes conceptual issues covered during the workshop, discusses a framework for how individuals and households allocate their time, and comments on some conceptual issues in measuring time use.
Keywords: Industry and Labor; Behavioral and Social Sciences

Women in the Chemical Workforce: A Workshop Report to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2000)
For a period of history no women worked outside the home. Bust as years have gone by and society has changed, Women are working varying jobs every day. They are, however, underrepresented in some sectors of jobs. This includes women in the engineering and science fields. To matters worse, women do not ascend the career ladder as fast as or as far as men do. The impact of this and related problems for science, the academic enterprise, the U.S. economy, and global economic competitiveness have been recently examined. The Chemical Sciences Roundtable evaluate that the demographics of the workforce and the implications for science and society vary, depending on the field of science or engineering. The roundtable has organized a workshop, "Women in the Chemical Workforce," to address issues pertinent to the chemical and chemical engineering workforce as a whole, with an emphasis on the advancement of women. Women in the Chemical Workforce: A Workshop Report to the Chemical Sciences Roundtable includes reports regarding the workshop's three sessions—Context and Overview, Opportunities for Change, and Conditions for Success—as well as presentations by invited speakers, discussions within breakout groups, oral reports from each group.
Keywords: Industry and Labor; Behavioral and Social Sciences; Math, Chemistry, and Physics

Summary of a Workshop on Information Technology Research for Federal Statistics - National Research Council (The National Academies Press, 2000)
Part of an in-depth study of how information technology research and development could more effectively support advances in the use of information technology (IT) in government, Summary of a Workshop on Information Technology Research for Federal Statistics explores IT research opportunities of relevance to the collection, analysis, and dissemination of federal statistics. On February 9 and 10, 1999, participants from a number of communities—IT research, IT research management, federal statistics, and academic statistics—met to identify ways to foster interaction among computing and communications researchers, federal managers, and professionals in specific domains that could lead to collaborative research efforts. By establishing research links between these communities and creating collaborative mechanisms aimed at meeting relevant requirements, this workshop promoted thinking in the computing and communications research community and throughout government about possibilities for advances in technology that will support a variety of digital initiatives by the government.
Keywords: Computers and Information Technology; Behavioral and Social Sciences; Surveys and Statistics